Structural Transformation and Inequality: A Sectoral Analysis for Low- and Middle-income Countries - Magwedere, Margaret Rutendo; Marozva, Godfrey (Review of Economic Analysis, 2024)
The study examined the impact of structural transformation to inequality using a panel of low- and middle-income countries from 1996 - 2018. The system generalised method of moments was used to determine the effect of value-added of each sector to income inequality for the countries in the study. Increase in value-added for the mining and construction sectors reduces inequality whilst inequality increased with an increase in value-added for the agriculture and manufacturing sectors. Thus, for the countries in this study mining and construction driven structural transformation has an inequality reducing effect whereas there is a possibility that further structural transformation has no effect to reducing inequality. This implies that there is a probability of an increase in inequality due to further structural transformation. The implication for policy is a consideration of a channel of structural transformation that is suitable for a specific economy.